Vulnerability of high-speed rail grid-connected system on branch potential energy transfer entropy. (28th October 2021) - Fan, Wen-Li; Xiao, Ye-Qi; He, Xiao-Feng; Li, Quan-You; Hu, Ping; Ye, Yu-Run
Abstract: With the spurt of the high-speed railway construction, vulnerability analysis of the high-speed rail grid-connected system cannot be underestimated, which is helpful to improve the security of power system by preventive effectively. Therefore, we propose a vulnerability evaluation method for the uncertain high-speed rail grid-connected system combining branch potential energy function and information entropy together. Firstly, we construct a probability model of the high-speed rail loads by the nonparametric kernel density estimation method according to the measured data of traction substation. Secondly, we establish a power system vulnerability evaluation model based on the branch potential energy transfer entropy considering the power system state variables such as voltage magnitudes, voltage phase angles and power flows. Finally, the simulations on the IEEE-39 bus system and an actual power system in China show that the transmission line connecting the two regions is more vulnerable subjected to the influence of the high-speed rail loads, and the grid-connected points of the high-speed rail loads close to the generator help to reduce the output of the balance generator. These provides auxiliary suggestions for the rationalization of grid-connected location of high-speed rail load, and has certain practical application values.